IJTIHAD POLITIK UMAR IBN AL-KHATTAB (Implementasi Fiqh Kontekstual dalam Pemerintahan Islam) - Thabrani, Abdul Mukti (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2015)
The function of a state, as law institution, is about to make certain the leader competence that is to continuously perform ijtihad (effort) as inseparable part siyasah syarâiyyah (the politic of government). This is completely a dynamic domain as well as able to create flaming desire in the body of Islamic community since the era of khulafaur rasyidin up to present time. On the management of politics and government, it is undeniable that Islam appears as the most powerful force that finally takes to the great, authoritative, and accepted civilization in world politics.Â  In this context Umar Ibn al-Khattab became the champion. This article describes the form of political effort buildings of Umar Ibn al-Khattab manifested maslahah mursalah as an integral part and the destination of Islamic governmentâs political concept.Â Â  It also turned to be political effort priority at any fields, the implementation of contextual fiqh (Islamic law) in the Islamic government from the perspective of siyasah syarâiyyah meaning context as the basis of public prosperity and profits.